Correlation between Transient Response and Neuromorphic Behavior in Organic Electrochemical Transistors. (13th January 2022) - Yamamoto, Shunsuke; Polyravas, Anastasios G.; Han, Sanggil; Malliaras, George G.
Abstract: The factors controlling the neuromorphic response of organic electrochemical transistors (OECTs) are examined. In these devices, the gate voltage is used to supply the pre‐synaptic input, while the drain current is taken as the post‐synaptic output. The behavior of devices made from polymer blends of a mixed conductor (PEDOT:PSS) and an ion conductor (PSSNa) is analyzed. The experimental results highlight that the post‐synaptic response timescale depends on the size of ion in the electrolyte. Modeling shows that the neuromorphic response is controlled by the transient response of the ionic circuit of the OECT. These insights on device response time pave the way for a more rational design of OECT‐based neuromorphic devices. Abstract : The factors controlling the neuromorphic response of organic electrochemical transistors (OECTs) are investigated. The results highlight that the post‐synaptic response timescale depends on ion size in the electrolyte. Modeling shows that the neuromorphic behavior is controlled by the transient response of the ionic circuit of the OECT. These insights pave the way for a rational design of OECT‐based neuromorphic devices.